Coupling between side chain interactions and binding pocket flexibility in HLA-B*44:02 molecules investigated by molecular dynamics simulations. Issue 2 (February 2015) - Ostermeir, Katja; Springer, Sebastian; Zacharias, Martin
Graphical abstract